Glycosyltransferases and Transporters that Contribute to Proteoglycan Synthesis in Drosophila Identification and Functional Analyses Using the Heritable and Inducible RNAi System. - Nishihara, S. (Methods in Enzymology, 2010)
Drosophila melanogaster is an important model organism that can be used as a powerful genetic tool to analyze the physiological functions of various molecules. Recently, many successful analyses of the function of glycans in vivo have been performed using Drosophila. The glycan portion of proteoglycans, namely glycosaminoglycans (GAGs), which include heparan sulfate (HS) and chondroitin sulfate (CS), is conserved structurally between Drosophila and mammals, including humans. The analysis of mutant and RNAi flies has demonstrated that HS proteoglycans play key roles in the regulation of various basic developmental signaling pathways, including those of fibroblast growth factor (FGF), Wingless (Wg)/Wnt, Hedgehog (Hh), and Decapentaplegic (Dpp, a BMP-type ligand that belongs to the TGFbeta family). In this chapter, I give an overview of glycosaminoglycan biosynthesis in Drosophila and then describe the methods that can be used to identify and perform functional analyses of the molecules involved in this process, namely glycosyltransferases, sulfotransferases, sugar-nucleotide transporters including PAPS transporters, and core proteins, using the heritable and inducible RNAi system.